BASLAWÍSH KLASS OQÍTÍWSHÍLARÍN TAYARLAWDA KREDIT MODUL SISTEMASÍNDA ÓZ BETINSHE JUMÍS TÚRLERIN SHÓLKEMLESTIRIW METODIKASÍ - Kazakbayeva, N.A. (SCIENCE and SOCIETY, 2025)
The article is aimed at organizing independent work in the credit-module system in the training of elementary school teachers. It proposes a methodology for organizing independent work in the traditional form within the credit-module system.